1994
DOI: 10.1148/radiology.193.1.8090922
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of focal liver lesions: role of spin-echo and contrast-enhanced dynamic MR imaging.

Abstract: A specific diagnosis of liver lesions can be obtained in most cases by combining parameters obtained from SE and dynamic MR images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 0 publications
1
45
0
1
Order By: Relevance
“…The lesions were hypodense in 71% of the cases observed in our study (n=5) and isodense in 29% cases (n=2) in plain study and they showed early discontinuous peripheral enhancement in arterial phase with progressive centripetal filling in the delayed phase in all the cases as described by Hanafusa et al 9 and Yashimata et al 10 in their studies. The peripheral enhancement of the lesions was equal to the attenuation of aorta in all the phases studied.…”
Section: Haemangiomasupporting
confidence: 76%
“…The lesions were hypodense in 71% of the cases observed in our study (n=5) and isodense in 29% cases (n=2) in plain study and they showed early discontinuous peripheral enhancement in arterial phase with progressive centripetal filling in the delayed phase in all the cases as described by Hanafusa et al 9 and Yashimata et al 10 in their studies. The peripheral enhancement of the lesions was equal to the attenuation of aorta in all the phases studied.…”
Section: Haemangiomasupporting
confidence: 76%
“…Emphasis has been given to conventional "%weighted MR imaging for tissue characterization of focal liver lesions, with both qualitative and quantitative measures employed (1,2,11, 13,[29][30][31][32][33][34][35]. However, morphologic characterization does not always allow discrimination between malignant and benign lesions (especially if both have prolonged T 2 relaxation times) and quantitative measurements have been helpful in specific conditions (1 4).…”
Section: Discussionmentioning
confidence: 99%
“…Classically, HCC is characterized by arterial enhancement with washout on delayed venous phases [16,17]. On MRI, small HCC lesions tend to be isointense with rapid contrast enhancement, but larger HCC nodules may instead appear T1 hypointense and T2 hyperintense [18,19].…”
Section: Target Identificationmentioning
confidence: 99%